Layer-specific analysis of dobutamine stress echocardiography for the evaluation of coronary artery disease. Issue 32 (August 2016) - Park, Jae Hun; Woo, Jong Shin; Ju, Shin; Jung, Su Woong; Lee, Insoo; Kim, Jin Bae; Kim, Soo Joong; Kim, Weon; Kim, Woo-Shik; Kim, Kwon Sam
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Although dobutamine stress echocardiography (DSE) is a well-defined tool for the diagnosis of coronary artery disease (CAD), false-negative and false-positive results still occur. This study investigated the diagnostic role of layer-specific analysis using 2-dimensional speckle-tracking echocardiography (STE) during DSE. A total of 121 patients who underwent DSE and showed normal wall motion and ejection fraction during baseline echocardiography were enrolled. All patients underwent coronary angiography after DSE within 2 weeks. The patients were divided into the following 4 groups according to DSE results and CAD status: negative DSE with no significant CAD (n = 73), positive DSE with significant CAD (n = 16), negative DSE with significant CAD (n = 17), and positive DSE with no significant CAD (n = 15). Layer-specific global longitudinal strain (GLS) was assessed in the endocardium, mid-myocardium, and epicardium by STE techniques. Patients with significant CAD were older, more male and showed higher glucose level compared to patients without CAD. But coronary risk factors and previous medications were not different between patients with and without CAD. There were no significant differences in whole myocardium or layer-specific GLS found in the baseline echocardiography. During recovery echocardiography, endocardial GLS was significantly different between patients with and without CAD, regardless of the DSE results. A receiver-operating characteristic curve analysis showed that endocardial GLS (>−16%) was superior for identifying significant CAD during the DSE recovery stage. Diagnostic accuracy was improved by applying the results of endocardial GLS compared with visual estimation of DSE. The assessment of layer-specific strain by STE during DSE was feasible, and the evaluation of poststress endocardial function is a more sensitive tool for the detection of CAD.